2003
DOI: 10.1053/sder.2003.50012
|View full text |Cite
|
Sign up to set email alerts
|

Topical photodynamic therapy: A new tool in cosmetic dermatology

Abstract: Topical photodynamic therapy is an evolving relatively new modality in dermatology. While widely used in Europe for treatment of actinic keratoses and skin cancer, topical photodynamic therapy is still relatively unfamiliar in the United States. Approved by the US Food and Drug Administration in 1999, photodynamic therapy is now being evaluated for superficial epidermal tumors, acne, and cosmetic applications. This article reviews recent advances in this field, with emphasis on skin rejuvenation, acne, and hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 16 publications
1
25
0
5
Order By: Relevance
“…Alopecia areata (hair-loss condition of the scalp and body) does not respond generally to ALA/ MAL-PDT (26). Moreover, some dermatological clinics use ALA-PDT for hair removal (27). Accordingly, we think that our study concerning MN use in topical PDT is the first clinical study.…”
Section: Introductionmentioning
confidence: 86%
“…Alopecia areata (hair-loss condition of the scalp and body) does not respond generally to ALA/ MAL-PDT (26). Moreover, some dermatological clinics use ALA-PDT for hair removal (27). Accordingly, we think that our study concerning MN use in topical PDT is the first clinical study.…”
Section: Introductionmentioning
confidence: 86%
“…38 The light sources used in PDT for rejuvenation include lamps that emit broad spectrum visible light, red light, blue light, argon lasers, PDL and IPL. 39,40 In the treatment of photo-aging, IPL is able to improve different components of photo-damage except AK. The association of a photosensitizer such as ALA or MAL with an IPL device would therefore be capable of successfully treating all the components of photo-damaged skin.…”
Section: Photo-damaged Skinmentioning
confidence: 99%
“…Even when the photosensitizer is used only on the AK lesion, an improvement may also be seen around the lesion. 39 Ruiz-Rodriguez et al 41 reported on the use of 20% ALA incubated for four hours and IPL (filter of 615 nm) for AK in 17 patients with photo-damaged skin. The patients were submitted to two treatment sessions at a one-month interval.…”
Section: Photo-damaged Skinmentioning
confidence: 99%
“…97,99,100,[109][110][111][112][113][114][115][116] PDT is also used for the treatment of cutaneous T-cell lymphoma, 117 acne, 96,118 and photorejuvenation. 119,120 For the treatment of nonmalignant skin conditions, PDT is used for the stimulation of immunomodulatory effects in Nd: YAG neodymium yttrium aluminum garnet, KTP potassium titanyl phosphate, Er:YAG erbium-doped yttrium aluminum garnet, CO 2 carbon dioxide, LED light-emitting diode, IR infrared, RF radiofrequency, EMR electromagnetic radiation, NB-UVB narrowband UVB, PUVA psoralen + UVA …”
Section: Photodynamic Therapymentioning
confidence: 99%